Fungal Contamination and Aflatoxin B1 Detected in Hay for Dairy Cows in South Italy - Ceniti, Carlotta; Costanzo, Nicola; Spina, Anna Antonella; Rodolfi, Marinella; Tilocca, Bruno; Piras, Cristian; Britti, Domenico; Morittu, Valeria Maria (Frontiers in Nutrition, 2021)
The growth of filamentous fungi on fodder is recognized as responsible for fungal deterioration, and mycotoxin contamination of the plant mass leads to economic losses in the dairy cow production system. Mycotoxins have significant implications for human and animal health and is one of the major concerns in the food and feed chain. This research provides an insight into the variety of viable moulds (i.e. filamentous microfungi) that can be isolated from hay produced in South Italy and destined to dairy cows. On different lots of hay (n=55) collected from 20 dairy farms, a total of 33 different fungal species were identified. The most representative was Cladosporium cladosporioides (n=46; 84%) followed by Alternaria alternata (n=25; 45%) and Rhizopus stolonifer (n=24; 44%). The species most closely related to aflatoxin contamination, Aspergillus flavus, was isolated (n=11; 20%). Regarding aflatoxin detection, all hay samples were found to be scarcely contaminated by AFB1 and showed values from 0.0020 to 0.0077 mg/kg, below the limits established by EU legislation (0.021 mg/kgppm). None of the samples positive for Aspergillia and tested for AFB1 showed results exceeding established limits. Additionally, hay with moisture between 15.0 and 19.2% or crude ash on dry matter content ranging from 14.0 to 15.5% reported an increased presence of AFB1 (p<0.05) compared to the other samples. All the analysed hay samples, besides the presence of moulds, can be considered safe for the presence of AFB1. Prevention of mould spoilage is mandatory to reduce the exposure of human and animal to mycotoxins.